The Impact of Servitization on Supply Chain Management in Aero-Engine Industry: Analysis of Rolls Royce’s Case Study - Mahmood, Othman Kareem (2012)
Abstract: Objective: The objective of this dissertation is to examine how implementing servitization might affect supply chain management in aero engine industry. By critically reviewing the literature of both of servitization, supply chain and any relevant subtopics to aero engine industry such as MR&O services, and creating value. Moreover, by analysing Rolls Royce’s case study to examine the impacts of TotalCare program as an application of servitization on the three main elements of their supply chain management, supply network structure, management processes, and components. It aims to draw guidance from the literature and the practical case study for optimisation of implementing servitization with respect to the three elements of supply chain management, along with servitization to create value for the entire stakeholders. Methodology/design/approach: a qualitative methodology is used to approach this study as the problem can be analysed critically to link between different variables of the dissertation. A single case study method is used due to the nature of the main question highlighted, which is (How). Data collected mainly from the journals and publications online and three topics of servitization, supply chain management, MR&O. papers, articles, online articles, whitepapers, and work papers are all relevant to those three titles reviewed to aid in designing the case study from the formal website of Rolls Royce. the selection is rationalised by the fact that the result oriented type of servitization which focus on providing functionality is successfully applied by R-R. Moreover, as a second large manufacturing company worldwide, it has a complex product and supply chain, long age, broad install based units and an infrastructure of MR&O system. Three relevant literatures reviewed and links found to support the case study, analysis, and discussion. Findings/Value/Suggestions This dissertation found that implementing servitization would change the significance consequent of supply chain management elements; Information flow infrastructure will gain the lion share in importance as a glue to link all elements and components and organise Risk management as a new process. Competitors are also considered as a supplier partner to create or deliver value. Settlement 4 of Accounts between Banks is modified to organise the outsourced MR&O between competitors, and gain fully reliability and availability as a global network, with maintaining their customers. Firms must consider reengineering the organisation and the supply network with the implementation servitization type in accordance to the nature of the business. Future research should be on the drawbacks of entrepreneurs’ servitization rather than shifting of manufacturing to servitization. Key words Servitization, Supply Chain Management (SCM), Value Creation, Maintenance, Repair, and Overhaul (MR&O).